An Overview of Academic Procrastination in High School Students: Gambaran Prokrastinasi Akademik pada Siswa Sekolah Menengah Atas - Handoko, Puput Eka Wati; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the description of academic procrastination at SMA Di Ngoro Mojokerto. This research is a quantitative descriptive approach. This type of research uses a statement questionnaire. The number of samples in this study were 247 students. The results showed that the level of academic procrastination in high school students showed that the level of academic procrastination of students was dominated in the moderate category with a percentage of 37%, or equivalent to 89 students. Furthermore, 35% belong to the high category, and 29% belong to the low category. This means that students' academic procrastination mostly moves from moderate to high.